Pengaruh Fee Audit, Audit Tenure, dan Rotasi Audit Terhadap Kualitas Audit pada Perusahaan LQ45 yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023 - Faza Muraya Zuhru; Hairul Anam; Dika Karlinda Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine the influence of audit fees, audit tenure and audit rotation on audit quality in LQ45 companies listed on the Indonesian Stock Exchange in 2020-2023. The data used in this research is quantitative data with secondary data sources obtained from the audited financial reports and annual reports of the LQ45 Company on the official website of the Indonesia Stock Exchange and the official websites of each company. The sampling technique used purposive sampling technique and a sample of 23 companies was obtained with 92 observation data. Based on the results of the logistic regression test using the SPSS 25 application, it shows that audit fees have a significant effect on audit quality, while audit tenure and audit rotation do not have a significant effect on audit quality.